81 An Audit of Venous Thromboembolism (VTE) Risk Assessment & Prophylaxis Implementation. (28th February 2022) - Woolner, B.; Moore, P.; Parker, S.
Abstract: Introduction: VTE is considered one of the most common preventable causes of death and significant co-morbidity in inpatients and is responsible for approximately 60, 000 deaths occur per annum in the UK. The NHS Standard Contract requires all inpatients to undergo a VTE risk assessment, with a 95% patient assessment threshold. In January 2020 we identified that 72% of patients within our trust had a risk assessment completed, and 15% of these were accurate. We subsequently implemented mandatory VTE prescribing training for all junior doctors joining the trust. Aim: Review the impact of mandatory training module on VTE risk assessment and prescribing, in compliance with NICE Guidelines. Method: All inpatient medical notes, VTE risk assessments, and VTE prescriptions were reviewed to assess accurate risk assessment completion and subsequent appropriate prophylaxis prescribing. The standards were as set out in the NICE guidelines [NG89]. Paediatric, Obstetric and ITU patients were excluded. Results: Our VTE risk assessment completion rates increased from 72.1% to 94.2%, and the accuracy of these assessments from 15.4% to 34.5%. Our prescription rate increased from 84.6% to 90.6%, and prescribing accuracy from 41.2% to 79.5%. Conclusions: By implementing mandatory VTE prophylaxis training for all junior doctors joining a new NHS trust, we can see increased compliance with appropriate risk assessment and prophylaxis prescribing. This will reduce the risk of unnecessary death from VTE in hospital inpatients.